N-Tosyl-1,2,3-triazoles as Scaffolds for Morpholines: The Total Synthesis of (–)-Chelonin A - Gunawan, Nina; Nutt, Michael J.; Bissember, Alex C.; Smith, Jason A.; Stewart, Scott G. (Synlett, 2023)
Substituted morpholine derivatives appear frequently in biologically active compounds and thus novel routes towards such structures are of great synthetic interest. Herein, we report the total syntheses of chelonin A, a morpholine-derived marine natural product with reported antibacterial and anti-inflammatory activity. The key step in this process was a rhodium carbenoid 1,3-insertion into a bromohydrin O–H bond, followed by annulation, leading to a 2,6-disubstituted-3,4-dihydro-2H-1,4-oxazine core. This work was then extended to deliver the first asymmetric total synthesis of (–)-chelonin A using an enantioenriched bromohydrin, prepared in turn via asymmetric transfer hydrogenation of an α-bromoketone.
Keywords: chelonin A; morpholine; total synthesis; rhodium catalysis; triazole; asymmetric transfer hydrogenation